Protein nanowires with conductive properties1. Issue 25 (7th July 2015) - Elfwing, Anders; Bäcklund, Fredrik G.; Musumeci, Chiara; Inganäs, Olle; Solin, Niclas
<x xml:space="preserve">Abstract</x> We have investigated protein fibrils decorated with metallic polymers using conductive AFM.